Charting the Path of Financial and Monetary Economics: A Bibliometric Examination of Publication Patterns and Research Productivity - Ariawan, Ariawan; Sudarmanto, Eko; Muhammad Syafri; Samalua Waoma (Eastasouth Institute, 2023)
The dynamic landscape of financial and monetary economics has witnessed an evolution marked by scholarly publications that delve into the intricate dynamics of financial systems, monetary policies, and their far-reaching implications. Employing bibliometric analysis, this study maps the trajectory of these fields by scrutinizing publication patterns, research collaborations, influential authors, and emerging research areas. The analysis of comprehensive datasets derived from reputable academic databases provides a comprehensive view of the growth trends, collaborative networks, and research themes within the realm of financial and monetary economics. Utilizing a range of bibliometric indicators and visualization techniques, this research uncovers the historical journey and prevailing patterns that have shaped these vital domains. The findings of this study hold significance for researchers, policymakers, and academic institutions, aiding informed decision-making, innovative research, and effective policy formulation.